2017
DOI: 10.1002/wsbm.1385
|View full text |Cite
|
Sign up to set email alerts
|

Virtual endovascular treatment of intracranial aneurysms: models and uncertainty

Abstract: Virtual endovascular treatment models (VETMs) have been developed with the view to aid interventional neuroradiologists and neurosurgeons to pre-operatively analyze the comparative efficacy and safety of endovascular treatments for intracranial aneurysms. Based on the current state of VETMs in aneurysm rupture risk stratification and in patient-specific prediction of treatment outcomes, we argue there is a need to go beyond personalized biomechanical flow modeling assuming deterministic parameters and error-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 210 publications
(430 reference statements)
0
10
0
Order By: Relevance
“…Wall distensibility was not considered in this study, partially due to the growing consensus that compliance in the aneurysmal wall has a smaller influence on intracranial aneurysm flow than most of the other sources of uncertainty in patient-specific models, such as patient parent vessel flow, segmentation error in the analysis, etc. In a summary of studies comparing the differences between rigid-wall and fluid–structure interaction simulations of cerebral aneurysms, Sarrami-Foroushani, Lassila & Frangi (2017) showed that the rigid-wall assumption often results in a small overestimation of haemodynamic metrics of the order of 10 %, such as wall shear stress, but that the main flow features are preserved. In an experimental analysis of the flow inside untreated cerebral aneurysms, the addition of wall compliance was shown to affect the phase shift of the flow fields and the development of small-scale flow features near the aneurysm wall that were not found in the rigid model (Tupin, Saqr & Ohta 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wall distensibility was not considered in this study, partially due to the growing consensus that compliance in the aneurysmal wall has a smaller influence on intracranial aneurysm flow than most of the other sources of uncertainty in patient-specific models, such as patient parent vessel flow, segmentation error in the analysis, etc. In a summary of studies comparing the differences between rigid-wall and fluid–structure interaction simulations of cerebral aneurysms, Sarrami-Foroushani, Lassila & Frangi (2017) showed that the rigid-wall assumption often results in a small overestimation of haemodynamic metrics of the order of 10 %, such as wall shear stress, but that the main flow features are preserved. In an experimental analysis of the flow inside untreated cerebral aneurysms, the addition of wall compliance was shown to affect the phase shift of the flow fields and the development of small-scale flow features near the aneurysm wall that were not found in the rigid model (Tupin, Saqr & Ohta 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If normative flow boundary conditions are used instead, derived quantities of flow, such as WSS, may incur large errors and uncertainties. In the context of intracranial aneurysm flow modelling, previous meta‐analysis showed that the use of patient‐unspecific boundary conditions leads to a moderate‐sized effect (Hedges' g =0.30) when evaluating WSS patterns on the aneurysmal endothelium. This uncertainty can be multiplied by the presence of within‐subject flow variability.…”
Section: Discussionmentioning
confidence: 99%
“…Another study observed that flow rate variability has an effect on the predicted performance of flow diverters in the treatment of intracranial aneurysms. Such results indicate that both the flow variability and the specific demographics of the target patient population should be taken into account in vascular CFD simulations …”
Section: Introductionmentioning
confidence: 96%
“…The Navier-Stokes equations that describe the flowing blood are solved by a commercial CFD software package (Fluent, ANSYS Inc., Cannonsburg, PA, USA) under the assumptions of an incompressible Newtonian fluid. Although blood is a non-Newtonian fluid, it has been shown that the Newtonian fluid assumption works well for arteries over 3 mm in diameter and under normal hematocrit conditions (Sarrami-Foroushani et al 2017). Therefore, for the specific vessels under consideration in our simulation, blood is treated as a Newtonian fluid without loss of accuracy in the hemodynamic results.…”
Section: Methodsmentioning
confidence: 99%